A review on rules for examination of licensing criteria for producing foods for special medical purpose in China - Lei Wu; Lantian Zhang; Yan Zhang (Food Science and Human Wellness)
In this paper, the background, principles, and main contents of the rules for the examination of production licenses of foods for special medical purposes are introduced. The contents including general rules, production sites, equipment facilities, equipment layout, technological process, personnel management, management system and supplementary rules are interpreted item by item. This study has important value and historical significance for promoting the development of Chinese enterprises and industries of foods for special medical purposes. Keywords: Review, Foods for special medical purposes, Criteria of production, Examination of licensing